A mare's nest : broken promotion promise at Combitech, India - Goparaj, Hemanth; Sharma, Radha R., active 2020 (London : NeilsonJournals Publishing, 2020)
The case presents an employee's rights situation in India that occurred at one of the units of Combitech, an international commercial real estate group. An employee approached the compliance team with a complaint after a promise had been made and then broken by the vertical head and site director with respect to the employee's career progression. The Group HR Head flies from the U.S. to India and attempts to get to the bottom of the issue by talking to everyone involved. Issues regarding communication between department heads, leadership, and responsibility arise.
Originally Published InGoparaj, H., & Sharma, R. R. (2020). A Mare's Nest: Broken Promotion Promise at Combitech, India. Journal of Organizational Behavior Education, 13(1), 61-68. JOBE13-CS3.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Employee rights -- India -- Case studies